HPLC Identification of Mare’s Milk and Its Mix with Cow’s Milk - Vladimir P. Kurchenko; Elena S. Simonenko; Natalia V. Sushynskaya; Tatsiana N. Halavach; Andrey N. Petrov; Sergey V. Simonenko (Техника и технология пищевых производств, 2021)
Introduction. Mare’s milk is a valuable food product with medicinal properties. In combination with cow’s milk, it is used to create new functional foods. Efficient identification of mare’s milk, cow’s milk, and their mixes prevent falsification. Study objects and methods. The protein composition of mare’s and cow’s milk whey and their mixes was analyzed by high performance liquid chromatography (HPLC) using an Agilent 1200 chromatograph with an Agilent G1315C diode array detector. Separation was performed using a column Machinery Nagel C 18 4.6×250, 5 μm. Results and discussion. The standard HPLC method was optimized to analyse whey proteins in the milk samples. The separation of whey proteins included the following optimal parameters: chromatography time = 60 min, linear gradient of acetonitrile concentration = 0–50%, and sample volume for injection = 20 μl. Alpha-lactoalbumin proved to be the protein of mare’s milk and cow’s milk. The retention time of mare’s α-lactoalbumin was 45.16 min, and that of cow’s milk – 40.09 min. The differences in the retention time of α-lactoalbumin were associated with the presence of 33 amino acid substitutions in the primary structure of both milks. The areas of α-lactoalbumin peaks were used to calculate the amount of cow’s milk added to mare’s milk and the related percentage. Conclusion. A HPLC analysis of whey proteins made it possible to determine up to 50 mL of added cow’s milk in 1 liter of mare’s milk.